PERILAKU CYBER ROMANCE DITINJAU DARI STATUS IDENTITAS EGO DAN SIKAP TERHADAP PORNOGRAFI PADA REMAJA - Nurhidayah, Siti; Pramintari, Ratna Duhita (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Cyber romance is the activity of a person to develop feelings of love , attraction, closeness feeling ,etc, in accordance with aspects of intimacy , passion , and commitment to others in cyberspace . Teenagers do not know and understand who he really was in the midst of relationships and social structures ( ego identity status ). On the other hand the exposure of  pornography being one challenges for teenagers today's. The purpose of this study is to analyze the behavior of cyber romance in terms of ego identity status and attitudes towards pornography. The results showed that identity status (dimension of commitment) have significantly negative effect on the behavior of cyber romance. Age and attitudes toward pornography has a positive and significant impact on the behavior of cyber romance